2012
DOI: 10.1007/s10800-012-0424-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical properties of microwave-assisted reflux-synthesized Mn3O4 nanoparticles in different electrolytes for supercapacitor applications

Abstract: The nanosized Mn 3 O 4 particles were prepared by microwave-assisted reflux synthesis method. The prepared sample was characterized using various techniques such as X-ray diffraction (XRD), Fourier transform-infrared spectroscopy (FT-IR), Raman analysis, and transmission electron microscopy (TEM). Electrochemical properties of Mn 3 O 4 nanoparticles were investigated using cyclic voltammogram (CV), electrochemical impedance spectroscopy (EIS), and galvanostatic charge-discharge analysis in different electrolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 48 publications
4
64
0
Order By: Relevance
“…7). Additionally, the specific capacitance of sample a was larger than that of Mn 3 O 4 prepared by the microwave-assisted reflux synthesis method [30], which was highly aggregated and usually larger than 50 nm, leading to a lower specific surface area and specific capacitance. The galvanostatic charge-discharge curves of sample a at different current densities are shown in Fig.…”
Section: Electrochemical Performancesmentioning
confidence: 93%
“…7). Additionally, the specific capacitance of sample a was larger than that of Mn 3 O 4 prepared by the microwave-assisted reflux synthesis method [30], which was highly aggregated and usually larger than 50 nm, leading to a lower specific surface area and specific capacitance. The galvanostatic charge-discharge curves of sample a at different current densities are shown in Fig.…”
Section: Electrochemical Performancesmentioning
confidence: 93%
“…The shape of the CVs is quasirectangular, which confirms that the electrochemical reaction in Mn 3 O 4 electrodes have reversibility with KOH electrolyte. 9 It was found that the current density increases with an increase in the scan rate and reaches maximum for 20 mV s −1 . This shows that the voltametric current density is directly proportional to the scan rates of CV, which indicates the behaviour of an ideal capacitor.…”
Section: Study Of Electrochemical Responsementioning
confidence: 96%
“…Many reports on the synthesis and characterization of nanostructured Mn 3 O 4 through different routes for supercapactitor applications have appeared in the literature. [7][8][9] Specific capacitance as high as 314 F g −1 under low scan rates makes the material a potential candidate for supercapacitor applications. [8][9][10] Advantages of Mn 3 O 4 as a supercapacitor electrode material include good efficiency, long-term performance, low cost, environmental compatibility and good corrosion stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant transition metal oxides with nanostructures generally possess numerously highlighted physicochemical properties and have been applied widely in catalysts [1][2][3][4], electrochemistry [5,6], gas sensors [7,8], biomedical materials [9,10] and other fields. Of the oxides, nickel oxide (NiO), an important p-typed semiconductor with stable band gap, has received much attention and been extensively studied and used frequently as electrode for lithium ion batteries and funnel cells [11,12], catalysts [13][14][15], electrochemical supercapacitors [16,17], dyesensitized photocathodes [18], magnetic materials [19,20], etc.…”
Section: Introductionmentioning
confidence: 99%